2017
DOI: 10.1038/srep39782
|View full text |Cite
|
Sign up to set email alerts
|

Validation of suitable normalizers for miR expression patterns analysis covering tumour heterogeneity

Abstract: Oncogenic microRNAs (miRs) have emerged as diagnostic biomarkers and novel molecular targets for anti-cancer drug therapies. Real-time quantitative PCR (qPCR) is one of the most powerful techniques for analyzing miRs; however, the use of unsuitable normalizers might bias the results. Tumour heterogeneity makes even more difficult the selection of an adequate endogenous normalizer control. Here, we have evaluated five potential referenced small RNAs (U6, rRNA5s, SNORD44, SNORD24 and hsa-miR-24c-3p) using RedFin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…A seminal study demonstrated the utility of these molecules as biomarkers of adequate response to the treatment of OSA with continuous positive airway pressure (CPAP) [ 8 ]. However, prior to any analysis of circulating miRNAs, normalization is crucial due to the variability that occurs in plasma RNA isolation and analysis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A seminal study demonstrated the utility of these molecules as biomarkers of adequate response to the treatment of OSA with continuous positive airway pressure (CPAP) [ 8 ]. However, prior to any analysis of circulating miRNAs, normalization is crucial due to the variability that occurs in plasma RNA isolation and analysis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several molecules have been proposed as normalizers for miRNAs studies in different disorders, mainly in blood [ 36 ], plasma [ 37 , 38 , 39 ], cell cultures studies [ 25 , 40 ], tissue [ 41 ] and urine [ 35 , 42 , 43 , 44 ]. However, there is no consensus, even in the same sample type, regarding which is the best normalizer for miRNA studies.…”
Section: Discussionmentioning
confidence: 99%
“…The median of UniSp6 was used as a normalization factor to control for sample specific effects on assay performance and to calculate relative quantification levels of miRNAs. The choice of normalization factor was based on the availability of a common molecule in both panels, and its suitability as a reference for data analysis [21,23,[51][52][53].…”
Section: Data Preprocessingmentioning
confidence: 99%